Turn, Turn, Turn: A Digital History of German Historiography, 1950–2019. - Wehrheim, Lino; Spoerer, Mark; Jopp, Tobias A. (Journal of Interdisciplinary History)
The increasing availability of digital text collections and the corresponding establishment of methods for computer-assisted analysis offer completely new perspectives on historical textual sources and historiographical output. The results of a topic-modeling analysis exploring publication trends in eleven leading German-language history journals (around 9,000 original research articles) since World War II reveal several epistemological turns that had a measurable effect on historians' work.